Fecundity of northern shrimp Pandalus borealis dwelling at the west coast of Kamchatka - Oksana G. Mikhailova; Pavel Yu. Ivanov (Известия ТИНРО)
Fecundity of northern shrimp Pandalus borealis is investigated for the first time on the data collected from the depth 200-400 m near the coast of West Kamchatka in 2013-2014. The absolute and relative individual fecundity are determined, their relationship with size and age of the shrimp is analyzed. The individual fertility of females changes in limits of 1395-4648 eggs, with average number in the laying 2799 ± 190 eggs. The maximum fecundity is noted for females at the age of 7+. Losses of eggs for the northern shrimp at the west coast of Kamchatka don’t exceed 12 %.